2007
DOI: 10.1111/j.1365-2958.2007.05729.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and type III‐dependent secretion of the Yersinia pestis insecticidal‐like proteins

Abstract: SummaryPlague, or the Black Death, is a zoonotic disease that is spread from mammal to mammal by fleas. This mode of transmission demands that the causative agent of this disease, Yersinia pestis, is able to survive and multiply in both mammals and insects. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 51 publications
2
59
1
Order By: Relevance
“…Indeed, previous RT-PCR results indicated that there was no expression at 15 u C and thus the Tc complex present in this culture may be an artefact from the initial starter culture, which was grown at 28 u C. Most importantly these Western blots demonstrate that the toxin complex of strain IP32953 is secreted during growth in normal media at all temperatures. This indicates a mechanism independent of the plasmid-borne type III secretion system, which has been previously reported to be responsible for secretion of this complex and is only expressed at 37 u C (Gendlina et al, 2007) proteins. Thus it can be assumed that although this motif may contribute to binding, it does not determine cell specificity.…”
Section: C Hares and Othersmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, previous RT-PCR results indicated that there was no expression at 15 u C and thus the Tc complex present in this culture may be an artefact from the initial starter culture, which was grown at 28 u C. Most importantly these Western blots demonstrate that the toxin complex of strain IP32953 is secreted during growth in normal media at all temperatures. This indicates a mechanism independent of the plasmid-borne type III secretion system, which has been previously reported to be responsible for secretion of this complex and is only expressed at 37 u C (Gendlina et al, 2007) proteins. Thus it can be assumed that although this motif may contribute to binding, it does not determine cell specificity.…”
Section: C Hares and Othersmentioning
confidence: 92%
“…However, while Y. pseudotuberculosis is able to colonize the midgut of the rat flea and cause chronic infection, displaying symptoms such as diarrhoea, the heterologously expressed Y. pseudotuberculosis TcaATcaB [A] and TcaCTccC [BC] were found to lack toxicity to the flea. Furthermore, knockouts of these tc genes in Y. pseudotuberculosis strains did not diminish flea toxicity (Erickson et al, 2006(Erickson et al, , 2007 secreted via a type III secretion system indicative of immunomodulatory toxins although no functional data supporting this hypothesis have been published (Gendlina et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Using C-terminal glycogen synthase kinase (GSK) epitope tags fused to the N-terminal amino acid residues of the Y. pestis KIM TC-like protein's TCA (YitA and YitB), TCB (YitC), and TCC (YipA and YipB), Gendlina et al (27) identified that the GSK fusions are released by the Y. pestis type III system. The authors also found that under conditions optimal for type III secretion in Y. pseudotuberculosis, YitB could be detected in the culture supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that LrhA controls the transcription of this gene and that an xptD1 mutant displays attenuated virulence for M. sexta insects. Recent findings demonstrated that Yersinia pestis TC genes are regulated by YitR, a LysR-type regulator (but not a LrhA homolog) (25) and that the TC can be secreted through the type III secretion pathway. Therefore, it is plausible that, like the secretion of lipase, the X. nematophila TC, including XptD1, is secreted through the flagellar export apparatus.…”
Section: Discussionmentioning
confidence: 99%